Rydberg blockade in an ultracold strontium gas revealed by two-photon excitation dynamics - Qiao, Chang; Tan, Canzhu; Siegl, Julia; Hu, Fachao; Niu, Zhijing; Jiang, Yuhai; Weidemüller, Matthias; Zhu, Bing (Physical review, 2021)
We demonstrate the interaction-induced blockade effect in an ultracold 88Sr gas via studying the time dynamics of a two-photon excitation to the triplet Rydberg series 5sns3S1 for five different principal quantum numbers n ranging from 19 to 37. By using a multipulse excitation sequence to increase the detection sensitivity, we could identify Rydberg-excitation-induced atom losses as low as <1%. Based on an optical Bloch equation formalism, treating the Rydberg-Rydberg interaction on a mean-field level, the van der Waals coefficients are extracted from the observed dynamics, which agree fairly well with ab initio calculations.